Management of Pseudophakic Myopia Using Implantable Phakic Contact Lens with A ‘Piggy Back’ Technique - Kanchita Pandey; Devika Joshi; Shrikant Dinkar Joshi (Delhi Journal of Ophthalmology)
Purpose: We report a case of a pseudophakic myopic patient who received placement of an implantable phakic contact lens (IPCL) via a ‘piggyback technique’ resulting in improved visual acuity. Case report: A 35year old male patient with both eyes pseudophakic myopia came with complaints of diminution of vision in the right eye more than his left eye. After evaluating all available optical and surgical options, he received off-label placement of a posterior chamber IPCL with a piggyback technique for the pseudophakic right eye with a manifest refraction of -20.0 Ds. Best-corrected distance visual acuity improved from 20/60 to 20/30. Conclusion: Our case demonstrates the successful use of an implantable phakic contact lens (IPCL) in a pseudophakic myopic patient by a piggyback technique, resulting in improved visual acuity. This off-label use of IPCL offers a good alternative treatment option for pseudophakic patients with high refractive error.